2016
DOI: 10.1016/j.ecocom.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of field sampling design on variation partitioning in a dendritic stream network

Abstract: 16Variation partitioning is one of the most frequently used method to infer the importance of 17 environmental (niche based) and spatial (dispersal) processes in metacommunity structuring. 18However, the reliability of the method in predicting the role of the major structuring forces is 19 less known. We studied the effect of field sampling design on the result of variation 20 partitioning of fish assemblages in a stream network. Along with four different sample sizes, a 21 simple random sampling from a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…HLS, LLR). Nevertheless, it is possible that the EMS approach is just as sensitive to the spatial design of the study as to the method of variance partitioning of environmental and spatial fractions in the metacommunity context (see Sály & Erős, ). Consequently, while empirical studies on the structure of metacommunities are accumulating rapidly, we suggest that simulation‐based studies explore the sensitivity of the EMS analysis to the properties of the sampling design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HLS, LLR). Nevertheless, it is possible that the EMS approach is just as sensitive to the spatial design of the study as to the method of variance partitioning of environmental and spatial fractions in the metacommunity context (see Sály & Erős, ). Consequently, while empirical studies on the structure of metacommunities are accumulating rapidly, we suggest that simulation‐based studies explore the sensitivity of the EMS analysis to the properties of the sampling design.…”
Section: Discussionmentioning
confidence: 99%
“…Note, that we did not want to use variance partitioning to quantify the effect of spatial variables and hereby getting inferences on the effects of dispersal and/or drift (neutral stochasticity) mechanisms, since several studies (see Tuomisto & Ruokolainen, ; Gilbert & Bennett, ; Smith & Lundholm, ; Vellend et al ., for details), and our own simulations, specifically developed for stream networks (Sály & Erős, ), show that this method is not really reliably for this purpose. We believe that with the examination of DDRs (see below), we could more reliable quantify the importance of spatial distance on community composition and abundance and hereby getting some inferences on the role of dispersal limitation (Tuomisto & Ruokolainen, ).…”
Section: Methodsmentioning
confidence: 99%
“…To account for differences in sample sizes (Sály and Erős 2016), we included the total number of sites (total_SITES) as well as the total number of headwaters (total_HEADW) and downstream sites (total_RIVER) from each catchment. We also included catchment surface (SA) area as the relative importance of assembly processes may vary with spatial extent (Heino et al 2015) and we computed their latitude (LAT) and longitude (LONG) as the average latitude and longitude of their constituent sites, respectively.…”
Section: Regional Variables and Analysismentioning
confidence: 99%
“…Sály and Erös (2016) demonstrated that variation partitioning analysis is influenced by the number of sampling sites. Sály and Erös (2016) demonstrated that variation partitioning analysis is influenced by the number of sampling sites.…”
Section: Discussionmentioning
confidence: 99%